Prevalence and resistant patterns of multidrug-resistant urinary tract infection caused by Escherichia coli among patients admitted to a teaching hospital - Ghosh, Ranjit Kumar; Paul, Priyanka; Hyder Ali, M.; Abdul Alim, M.; Hossain, Mobarak (International Journal of Research in Medical Sciences, 2023)
Background: Multi-drug resistant organisms, particularly in urinary tract infections, have become a significant concern in developing countries like Bangladesh. Physicians are facing challenges in treating hospitalized cases due to the ineffectiveness of conventional antibiotics and empirical treatment, as well as the emergence of multi-drug-resistant Escherichia coli. The main goal of the study was to observe the prevalence and resistant pattern of multidrug-resistant Escherichia coli urinary tract infections among patients admitted to a teaching hospital. Methods: The cross-sectional study was conducted between August 2011 to February 2012 at Uttara Adhunik Medical College Hospital (UAMCH), Dhaka, Bangladesh. It included 100 cases, and detailed information was obtained through a standardized protocol. Results: In a study of 100 UTI patients, 45 had MDR E. coli while 55 had non-MDR E. coli. Females accounted for 79% of the patients, with a mean age of 44.85±17.81 years. The majority of participants fell into the 31-40 years age group (28%) and 60 years age group (23%). Among the participants, 57% had a history of UTI while 43% had no previous UTI history. High resistance was observed against amoxicillin, amoxiclav, cephradine, cefuroxime, cefixime, ceftriaxone, ceftazidime, and nalidixic acid. However, ciprofloxacin (2.22%), levofloxacin (6.67%), and cotrimoxazole (31.11%) exhibited lower resistance rates among MDR samples. Imipenem and meropenem showed 100% effectiveness against all MDR samples. Conclusion: MDR E. coli rates were alarmingly high in a teaching hospital in Bangladesh. Excessive antimicrobial drug consumption globally has led to antibiotic-resistant E. coli isolates, posing challenges for effective UTI treatment worldwide. Antibiotic therapy remains crucial in controlling these invasive agents.